PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUASAN PELANGGAN PADA ROLAG CAFE DIPONEGORO SURABAYA - Nano Gunawan; Chandra Kartika (Universitas 17 Agustus 1945 Surabaya, 2018)
This research is meant to examine the influence of service quality, price, and place to thecustomer satisfaction at Cafe Rolag Diponegoro Surabaya. The population of thisresearch is all customers who have ever visited at Cafe Rolag Diponegoro Surabaya. Theresearch samples has been obtained by using accidental sampling method. In according tothe predetermined criteria 100 respondents who have ever visited Cafe Rolag DiponegoroSurabaya have been selected as samples. The analysis method has been carried out byusing multiple linear analysis with SPSS application .The result of the model feasibilitytest which has been done by using F test has concluded that the research model is feasibleto be used for the following analysis. Meanwhile the result of hypothesis t test (partial)shows that service quality has significant influence to the customer satisfaction.And placehas significant influence to the customer satisfaction.Keywords: Service quality, place, and customer satisfaction.